Decomiso y Confiscación de los Productos de los Trabajadores Autónomos Vulnera Derechos Constitucionales - Mora Calle, Thalia Carolina (2016)
This research "Seizure and confiscation of the products of self-employed workers infringes constitutional rights," represents one of the most important economic phenomena in current times and has been taking place in the commercial economy of Latin American countries such as in our country and city. This research work was encouraged by the third paragraph of Article 329 of our constitution, which recognizes and guarantees self-employment, prohibiting all types of confiscations of products and materials that self-employed workers use as a means to work in public spaces. Sel-employed workers find it easier to work in public spaces because there is no need to make high payments for physical stores which end up hindering their business. The before mentioned rule is not respected by the municipal authorities and violates the rights of workers in this sector of the Ecuadorian trade. In the development of the literature review of this research topic the conceptual framework encompasses terms such as confiscation, seizure, work, self-employment, informal trade, constitutional rights, among others that are considered most important when addressing this problematic. Under the doctrinal framework the history of informal trade in Latin America and Ecuador, as well as the possibilities for development of this commercial sector and its transition to formality are several key points. Within the legal framework I describe the laws and regulations that are responsible for 5 protecting the rights of self-employed workers and control the informal trade in Ecuador. Comparative law includes comparing the Ecuadorian standards with the ones of other countries such as Peru, Colombia and Argentina regarding self-employed workers and their regulation. Field research allows us to confirm what the current situation of self-employed workers in our city is. The work of such individuals as their means of livelihood and every day survival face the violation of their rights and abuse by the municipal police. In addition, this research seeks the requirement of a penalty for the municipal police who come to the use of force when carrying out their operations. It is necessary that the Decentralized Autonomous Governments within their functions and responsibilities be in charge of regulating and protecting self-employed workers as a fundamental part of the economy. Given such needs it is of critical importance to present a proposal to reform the Organic Code of Territorial Organization, Autonomy and Decentralization, where the responsibilities of municipalities in favor of self-employed workers is established.